The diversity and ecological roles of insects and arachnids in arabica coffee (Coffea arabica) plantation in Palasari, Bandung Regency: Keanekaragaman dan fungsi ekologis serangga dan arachnida pada ekosistem kopi arabika (Coffea arabica) di Palasari, Kabupaten Bandung - Maharani, Yani; Dewi, Ajeng Putri Kusuma; Rasiska, Siska; Hutapea, Dedi; Maxiselly, Yudithia; Sandrawati, Apong (Jurnal Entomologi Indonesia, 2024)
The diversity of arthropod communities is often used as a bioindicator of environmental changes, specifically in coffee farms with various management systems. Significant impacts of the environmental changes lead to alterations in the community structure and function of arthropods. The aim of this research was to determine the diversity and ecological roles of insect and arachnids in arabica coffee plantations in Bandung Regency. Sampling was conducted on five plots measuring 100 m2 each, with a separating distance of 50 m, in coffee farms located in Legok Nyenang Village, Bandung Regency. This was performed five times per weekly intervals using sweep nets, yellow tray traps, and beating sheets. Subsequently, collected samples were identified based on morphological characters at the Pest Laboratory, Faculty of Agriculture, Padjadjaran University. A total of 269 insects species (11 orders and 98 families, total 669 individuals) and 23 species of Arachnida (one order and 13 families, total 44 individuals) were found, The most abundance of natural enemies were the parasitoid, Megacampsomeris prismatica (Hymenoptera: Scoliidae) and the predator, Tetragnatha sp. (Araneae: Tetragnathidae). Meanwhile, the ecological function of the group with the lowest number was pollinators (Hymenoptera: Apidae). Although the diversity of insects and arachnids species found in coffee farms was high (H' = 5.10), the evenness and dominance index were relatively low. These results showed the potential of coffee plantations as ecosystems for conserving predatory arthropods biodiversity. Consequently, coffee cultivation practices and pest management strategies must prioritize the protection of beneficial insects such as natural enemies and pollinators.